Determining stillbirth data reporting systems in Africa - Gumede, Simphiwe W (Division of General Surgery, 2025)
Background Stillbirths are an important public health concern, with an estimated 1.9 million stillbirths occurring globally each year, more between 2020-2021 data. However, the recording, investigation, and classification of stillbirths vary across countries, leading to inconsistencies in data collection and analysis. This study aimed to assess the current data systems and practices regarding stillbirth recording, data collection, analysis, and utilization in African countries. Study design The study used a descriptive research design with a quantitative approach, involving the surveillance of national data systems and other existing systems in African countries. Method The study was undertaken in African countries by University of Cape Town in collaboration with the Africa Centres for Disease Control and UNICEF. The study involved a survey of the national data systems recording stillbirths in the African countries and other reporting systems that countries use. Results A survey of 55 African countries (34 respondents) revealed critical insights into stillbirth reporting and data management. Among responding countries, 76% defined stillbirth using a gestational age threshold of ≥28 weeks, while 48% used a birth weight criterion of ≥1000 grams. Significant policy gaps were identified: 47% lacked mandates for stillbirth classification, and only 57% integrated stillbirth targets into national health strategies. Despite 88% of countries routinely collecting stillbirth data, methods varied (paper-based vs. digital), and 54% reported no data quality assessments in the past decade. Classification systems for causes of death varied, with ICD-PM and ICD-10 each used by 35% of countries. Nurses/midwives were primarily responsible for data entry (73%), yet challenges persisted, including inadequate health worker capacity (53%) and poor infrastructure (42%). Only 42% of countries disseminated stillbirth reports publicly, often relying on aggregated tables rather than interactive formats. Regional disparities underscored systemic issues in healthcare access, data standardization, and governance, emphasizing the urgent need for policy harmonization and strengthened health information systems. Conclusion The persistent inconsistencies in the recording, investigation, and classification of stillbirths and perinatal deaths across African countries-evident in different gestational age (20-28 weeks) and birth weight thresholds (<500g to <1000g), ambiguous civil registration laws (82% of countries), and fragmented national policies (only 27% with stillbirth-specific targets) highlight an urgent need for standardised definitions and consistent legal frameworks. These gaps perpetuate unreliable data, obstructing targeted interventions and accountability mechanisms. To address this, governments must adopt WHO-aligned criteria, integrate stillbirth reduction into national health strategies, and strengthen cross-sector collaboration for robust civil registration systems. Prioritizing these steps, alongside research into context-specific barriers (e.g., stigma, resource limitations), will not only improve data accuracy but also catalyse actionable insights to reduce preventable stillbirths and advance maternal and newborn health outcomes globally.